2006
DOI: 10.2527/2006.844938x
|View full text |Cite
|
Sign up to set email alerts
|

Residual feed intake of purebred Angus steers: Effects on meat quality and palatability

Abstract: Relationships between residual feed intake (RFI) and other performance variables were determined using 54 purebred Angus steers. Individual feed intake and BW gain were recorded during a 70-d post-weaning period to calculate RFI. After the 70-d post-weaning test, steers were fed a finishing ration to a similar fat thickness (FT), transported to a commercial facility, and slaughtered. A subsample of carcasses (n = 32) was selected to examine the relationships among RFI, meat quality, and palatability. Steers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
52
4
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 25 publications
18
52
4
10
Order By: Relevance
“…This result is consistent with the observation of Baker et al (2006) that, at a phenotypic level, reported RFI measured in Angus steers had no significant effect on objective tenderness measurements or taste panel scores. RFI had moderate genetic relationships with carcass composition traits (Table 7: r g = 0.49 with RIB, -0.42 with EMA and -0.61 with RBY), which were consistent across genotypes, suggesting that selection to improve RFI would produce carcasses which were genetically leaner, with larger EMA and higher RBY.…”
Section: Residual Feed Intake and Meat Quality And Carcass Traitssupporting
confidence: 82%
“…This result is consistent with the observation of Baker et al (2006) that, at a phenotypic level, reported RFI measured in Angus steers had no significant effect on objective tenderness measurements or taste panel scores. RFI had moderate genetic relationships with carcass composition traits (Table 7: r g = 0.49 with RIB, -0.42 with EMA and -0.61 with RBY), which were consistent across genotypes, suggesting that selection to improve RFI would produce carcasses which were genetically leaner, with larger EMA and higher RBY.…”
Section: Residual Feed Intake and Meat Quality And Carcass Traitssupporting
confidence: 82%
“…Feed intake and body size between divergent RFI groups Usually, the selection of cattle with low RFI decreased feed costs (Baker et al, 2006;Kundu et al 2014). Williams et al (2011) found that Holstein-Friesian dairy heifers with the 10% lowest RFI ate 1.7 kg less DM each day than the 10% highest RFI ones to achieve the same rate of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al (2006) reported that low RFI Angus steers consumed less dry matter (DM) when compared with high RFI steers. Herd and Bishop (2000) and Nkrumah et al (2007) also found that selecting low RFI phenotypes would reduce feeding costs.…”
Section: Introductionmentioning
confidence: 99%
“…RFI is calculated as the actual feed consumed minus the feed that the animal was expected to consume based on its mid-test weight and average daily gain (ADG). This measurement, which is expressed as the difference or residual, is phenotypically independent of growth rate and body weight in growing cattle (Kennedy et al, 1993;Arthur et al, 2001a,b;Archer et al, 2002;Herd et al, 2003;Baker et al, 2006). Most studies have found genetic independence as well (Herd and Bishop, 2000;Arthur et al, 2001b).…”
Section: Introductionmentioning
confidence: 95%